PENGARUH PEMBERIAN ASI EKSKLUSIF TERHADAP PERTUMBUHAN DAN PERKEMBANGAN BAYI - Desi Ernita Amru; Hazen Aziz; Larince Radulima Febrianti. S (Universitas Batam, 2022)
Exclusive breastfeeding is giving only breast milk immediately after birth until the baby is 6 months old and giving colostrum. Growth is the increase in the number and size of cells in all parts of the body that are quantitative and can be measured. Development is the complete increase in the function of the organs of the body. The purpose of this study was to see the relationship of exclusive breastfeeding to the growth and development process of infants in Batu Aji Public health center. The research method used is descriptive analytic with a cross sectional research design. The population of my study amounted to 182 infants. The sampling using purposive sampling technique as many as 60 infants. The data analysis technique used univariate analysis and bivariate analysis with chi square statistical test at a significant level of 0.05. The results showed that there was a significant effect between exclusive breastfeeding on the growth and development process of infants with P-value (0.00) < (0.05). The suggestion in this study is that mothers want to exclusively breastfeed their babies and not give any complementary foods until the age of 6 months.